Forecasting sales demand of new Proton car using bass diffusion model - Abu, Noratikah; Ismail, Zuhaimy (Pushpa Publishing House, 2018)
Forecasting new product or service is a critical process in marketing strategies and product performance for an organization. There are several forecasting methods to forecast new product or service and the common method use in industry nowadays is Bass diffusion model. Since the publication of the Bass diffusion model in 1969, innovation of new diffusion theory has sparked considerable research among marketing science scholars, operational researchers and mathematicians. This paper applied basic Bass diffusion model to make analysis and forecast for vehicle demand in Malaysia. The objective of the proposed model is to represent the level of spread on the new car among a given set of the societies in terms of a simple mathematical function that elapsed since the introduction of the new product. With the limited amount of data available for the new product, a robust Bass model was developed to forecast the demand. We discuss the selection of analogy product, selection of parameter estimation method and selection of different valued potential market. A procedure of the proposed diffusion model was designed and the parameters were estimated. Results obtained by applying the proposed model and numerical calculation show that the proposed Bass diffusion model is robust and effective for forecasting demand of new product. This study concludes that the newly developed Bass diffusion of demand function has significantly contributed for forecasting the diffusion of new product.